Anomali Prosedur Pemilihan Kepala Pemerintahan Negeri di Kecamatan Salahutu Kabupaten Maluku Tengah - Muhammad Husein Maruapey; Budiman Rusli (Jurnal Administrasi Publik (Public Administration Journal), 2018)
Research about Anomaly of Election Procedure of Head Village Government until now become unresolved social problem. Although the Policy of Regional Regulation Number 3 Year 2006 has been going on for a long time. The Local Government has made various breakthroughs, but is constrained by various problems. Among others, internal conflicts of indigenous peoples, lack of community support and the intrigue and interests of local political elites. The use of qualitative methods in this study is because the object under study requires direct observation of the researcher as the main instrument in addition to avoiding the occurrence of speculation and engineering research data, Based on the research, showing there are procedural deviations caused by several aspects such as: Saniri State Resources not yet qualified, implementing agencies are inconsistent with rules, halfhearted and unequivocal policies, external conditions of polarized community with policy the election of the village head implemented by the Soeharto government. The results of the research showing are related to factors (1) Human Resources not yet qualified, (2) Non-compliance with Rules, (3) Unclear policies, (4) with the Electoral Program of the New Order era (5) Intrik and interests of local political elites and (6) The history bias of the State Government.